Pendidikan politik dan pembentukan masyarakat inklusif-partisipatif dalam pembangunan demokrasi berkelanjutan - Bako, Anggreni; Hutabarat, Putra Kaslin; Rahmadini, Aulia; Aufa, Arsa; Nursaifa, Alia (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This paper aims to explore the strategic role of political education in fostering an inclusive and participatory civil society in Indonesia. Political education is one of the important instruments to develop civic awareness, increase active citizen participation, and strengthen civil society as a democratic foundation. Through literature analysis and library research, it highlights the political education's role in shaping an autonomous, critical and contributive society towards sustainable democratic development. However, political education in Indonesia remains exposed to various challenges, such as limited participatory curricula, limited educational access, and pedagogical barriers. Consequently, innovative strategies and government policy support are needed to strengthen the effectiveness of political education as an effort to empower civil society in Indonesia. In doing so, the study proposes practical recommendations for policy makers, educational institutions and civil society organizations to strengthen citizens as agents of social change and enhance democracy.